Juridical Analysis of the Judge'S Decision in the Narcotics Courier Case (Study of Decision Number 28/Pid. Sus/2025/Pn Sng) - Safitri Mudriyani, Ajeng; Dewi, Sartika; Abas, Muhamad (Dinasti Research, 2025)
Law enforcement against narcotics crimes in Indonesia is a complex and crucial issue, especially for perpetrators who act as drug couriers. This study aims to analyze the legal considerations used by judges in sentencing narcotics courier fraudsters, focusing on Decision Number 28/Pid.Sus/2025/PN Sng. Based on the results of a survey by the National Narcotics Agency (BNN), an average of 50 people die each year due to drugs. This means that around 18,000 people die per year from smoking. The approach used is normative juridical, by examining laws and regulations, legal literature, and court decisions. This study is descriptive qualitative in nature, aiming to provide an understanding of the application of Article 114 Paragraph (2) of Law No. 35 of 2009 concerning Narcotics in judicial practice. The results of the study show that in sentencing, judges consider various aspects, such as the role of fraudsters in the narcotics distribution network, the amount of evidence, and cooperative attitudes in selling narcotics. Although the legal provisions regulate severe sanctions against perpetrators of drug trafficking, there is still room for judges to proportionally assess the role of couriers in a crime. This analysis is expected to contribute to the development of criminal law, especially in creating a fair and effective justice system in members of drug crimes